The Impact of the Externality of Tofu Manufacturing Business on the Social, Economic, and Environmental Aspects of the Community - Nurliani Nurliani; Ida Rosada; Sitti Nurani Sirajuddin; Mukhlis Mukhlis (Jurnal Penelitian Pendidikan IPA, 2024)
The tofu industry is growing because it is a cheap and nutritious food, but the production process produces liquid and solid waste that is harmful to the environment. The research aims to describe the community's perception of the social, economic, and environmental conditions of the tofu-making business and calculate the value of community losses to maintain ecosystem value. This research uses survey and interview methods with communities in tofu production centers. Data analysis using the CVM method (Contingent Valuation Method) to estimate the costs that the community will pay. The research results show that the community's response around the tofu-making business to the social environment is in the category of not providing employment opportunities and children's education. The community's response to economic aspects is in the disagree category, meaning that the tofu-making business has no impact on increasing people's income and purchasing power. Respondents disagreed that tofu liquid waste disturbed the surrounding environment. Before being discharged into waterways, liquid waste goes through a processing process in a wastewater treatment plant (IPAL) so that liquid waste discharged into rivers is free from chemicals and odor. Meanwhile, solid waste is sold for animal feed. Value of willingness to pay (willingness to pay) community to maintain ecosystem value of IDR 80,450/year/KK.